Observation of enhanced field emission properties of Au/TiO2 nanocomposite - Patil, Girish P.; Bagal, Vivekanand S.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Applied Physics A-Materials Science & Processing, 2016)
Simple and low-cost method of thermal annealing was used to decorate Gold (Au) nanoparticles on aligned TiO2 nanotubes. The aligned TiO2 nanotubes were decorated by Au nanoparticles with an average diameter of 9, 18 and 28 nm (aligned TiO2 nanotubes referred as specimen A and TiO2 nanotubes decorated by Au nanoparticles with average diameter of 9, 18 and 28 nm are referred as specimen B, C and D, respectively). The detailed characterization such as structural, morphological and elemental analysis of TiO2 and Au/TiO2 nanocomposite have been carried out using X-ray diffraction, field emission scanning electron microscope, transmission electron microscope, X-ray photoelectron spectroscopy and Raman spectroscopy. Furthermore, the meticulous comparative field emission characteristics of the aligned TiO2 nanotubes and Au/TiO2 nanocomposite have been performed. The turn-on field defined for the current density of 10 mu A/cm(2) has been found to be 3.9, 2.8, 3.2 and 3.7 V/mu m for specimen A, B, C and D, respectively. The observed low turn-on field of specimen B has been found to be superior than the other semiconducting nanocomposites reported in the literature. The emission current stability over a period of 3 h is found to be better for all the specimens. To the best of our knowledge, a systematic field emission study of Au/TiO2 nanocomposite has not been explored. The observed superior field emission study of Au/TiO2 nanocomposite indicates their possible use in micro/nanoelectronic devices.